ChemInform Abstract: Synthesis, Crystal Structure and Electrical Proprieties of New Phosphate KCoP3O9. Issue 9 (March 2015) - Ben Smida, Y.; Guesmi, A.; Georges, S.; Zid, M. F.
Abstract Crystals of the new title compound are prepared by solid state reaction of K2CO3, Co(OAc)2·4H2O, and NH4H2PO4 in the molar ratio of K:Co:P = 1:1:3 (porcelain crucible, 300 °C in air for 12 h and 820 °C for 3 d).